2019
DOI: 10.18860/psi.v12i1.6396
|View full text |Cite
|
Sign up to set email alerts
|

Hope-Based Intervention untuk Menurunkan Stres Serta Meningkatkan Harapan dan Subjective Well-being pada Penderita Diabetes Mellitus Tipe 2

Abstract: Penelitian ini bertujuan untuk menguji efektivitas hope-based intervention untuk menurunkan stres serta meningkatkan harapan dan subjective well-being pada penderita diabetes mellitus tipe 2 menggunakan desain eksperimen pretest posttest control group design pada 20 orang penderita Diabetes Mellitus tipe 2 berusia 20-40 tahun. Alat ukur yang digunakan berupa skala stres adaptasi Perceived Stress Scale dari Cohen (1988), skala harapan adaptasi Hope Scale dari Snyder (2003) serta skala subjective well-be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
3
0
3
Order By: Relevance
“…In fact, the effectiveness of online counseling was greatly determined by factor of client trust. Research by Sosialita (2019) revealed that attitude towards counseling process was an important and significant for the success of group counseling process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the effectiveness of online counseling was greatly determined by factor of client trust. Research by Sosialita (2019) revealed that attitude towards counseling process was an important and significant for the success of group counseling process.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, midwives in Primary Health Care are required to complete some administrative tasks beside the first to service patients. As known, their workload automatically increased by some activities exclude doing service to patients, for instance some field activities like home care, immunization, health surveys, and so forth (Sosialita, 2016). The demands to complete all responsibilities which are exhausting can be a significant reason for midwives to feel physically and mentally exhausted.…”
Section: Introductionmentioning
confidence: 99%
“…In its development, GHQ has been translated into various languages and used in many countries, including Indonesia. Multiple studies that have been conducted prove that the validity and reliability of the GHQ are satisfactory (Sosialita & Hamidah, 2019). GHQ has four versions with different numbers of items for each performance.…”
Section: Data Collectionmentioning
confidence: 99%
“…Secara umum, uji beda dilakukan untuk melihat apakah skor yang diperoleh sasaran berbeda antara sebelum dan sesudah perlakuan, yaitu dengan membandingkan gain score kuesioner pengetahuan kewirausahaan yang telah dikerjakan oleh sasaran. Uji beda dilakukan dengan menggunakan teknik statistika, dimana jika data berdistribusi normal dan homogen maka teknik analisa data menggunakan statistik parametrik dan jika data tidak normal maka teknik analisa data menggunakan prosedur non parametrik (Sosialita & Hamidah, 2015).…”
Section: Gambar 3 Sharing Session Dengan Wirausaha Muda Secara Daringunclassified